The best interests of the child in “mixed” couples’ divorce in Belgium and the Netherlands - Asuncion Fresnoza-Flot (Oñati Socio-Legal Series)
Studies on the marital break-up of “mixed couples” in which partners have different nationalities and/or ethnicities pay little attention to how individual partners, notably the one with a migration background, experience the law and institutions concerning their children. Drawing on ethnographic observations and interviews with Filipino women in Belgium and the Netherlands, this paper investigates these migrants’ socio-legal experiences to shed light on their children’s situation during the divorce process. Paying attention to the principle of the “best interests of the child”, data analyses reveal that the children of women experiencing problematic divorce and/or domestic violence have more direct encounters with laws and/or institutions than those whose parents separated on good terms. Likewise, young people whose parent(s) resort to socio-legal assistance in their country of residence are more exposed to the legal aspects of divorce. This case study underlines the intersubjective dimension of divorce and suggests that state policies do shape individual lives.